Eating Habits of Carbohydrate and Protein Sources in Elementary School Children during the Pandemic - Ayu Mutiara Santanu; Hurry Mega Insani; Muchamad Rizki Sentani (Universitas Pendidikan Indonesia, 2021)
Elementary school children are children aged 6-12 years and had eating habits depend on their social life at school. Feeding habit in children consisted of mother’s beliefs about feeding, child feeding practices, and children’s eating behavior. children who consumed unhealthy food, such as snacks, relatively experienced low energy or calorie, while children with high consumption of unhealthy food tended to have a significant effect on experiencing health problem. The purpose of this study is to describe the eating habits of elementary school students from carbohydrate and protein sources during the pandemic. This study is a correlational study using a cross-sectional design. The population in this study were elementary school students at Mutiara Elementary School, Garuda Village, Andir District with a total of 95 students as respondents. The data collection tool in this study used a questionnaire. Data were analyzed descriptively. Carbohydrate sources that are often consumed by students are rice (100%), noodles (56.8%) and bread (53.7%). Sources of animal protein that are often consumed are chicken meat (74.7%) and chicken eggs (94.7%). Meanwhile, the most consumed vegetable protein was tofu (81.1%) and tempeh (67.4%). The food consumed by school-age children is less diverse. It is important for schools to provide education about the provision of diverse foods.